Platelet indices in patients with acute appendicitis: a systematic review with meta-analysis - Shen, Guixin; Li, Senjuan; Shao, Zhuo; Liu, Lianjie; Liu, Qizhi; Yu, Hang; Wang, Hao; Mei, Zubing (Updates in surgery, 2021)
Correlation between blood inflammatory parameters and acute appendicitis (AA) remains controversial. This meta-analysis aims to evaluate whether platelet (PLT) indices including mean platelet volume (MPV), PLT count, and platelet distribution width (PDW) are associated with AA. Pubmed, Embase, and Cochrane Library databases were searched for observational studies published from inception through April 2020 by two independent investigators. Studies reporting associations between platelet indices and AA were selected for inclusion. Standardized mean difference (SMD) and 95% confidence interval (CI) were estimated for continuous outcomes using a DerSimonian–Laird random-effects model. Of 842 records identified, 17 studies with a total of 6793 subjects met our inclusion criteria. Meta-analysis indicated that compared with those in healthy controls, significant decrease in MPV levels was observed in subjects with AA (SMD − 0.34; 95% CI − 0.56 to − 0.12; P = 0.003). Subgroup analyses represented a significant reduction of MPV levels in patients aged ≥ 30 years and non-complicated/non-perforated AA. Due to the small number of studies and patients included in each subgroup, these subgroup analyses need to be interpreted with caution. However, none of the levels of PLT (SMD − 0.13; 95% CI − 0.28–0.012; P = 0.071) or PDW (SMD 0.30; 95% CI − 0.22–0.83; P = 0.257) was seen decrease or increase in subjects with AA. This meta-analysis indicates a significant decrease in MPV levels in patients with AA, which makes MPV have the potential of serving as a biomarker for AA. The associations of other PLT indices with AA need to be further examined.